Las poblaciones de Pelecípodos del Arroyo Ayuí Grande (Prov. Entre Ríos) y los factores que regulan su distribución y estructura - Bonetto, Argentino A.; Di Persia, Danilo H. (Ecosur, 2025)
The present paper deais with studies on populations of all the species of Pelecypoda belonging to the superfamilies Unionacea, Mutelacea and Sphaeriacea, in the Ayuí Grande stream, a small tributary of the Uruguay River in the Entre Ríos Province (Argentina). There have been specially considcrcd thc population’s structurc and distribution, its relative density, and the changes happened localy through twenty four sampling places along the whole stream and its main tributary, the Loma Negra Stream, whieh made possible to appreciate the main variations recorded throughout the course. The most important factors that determine and regúlate the structurai composition of the populations and their spacial distribution, are also analized. According to the obtained results, the studied Pelecypoda constitute relatively unstablc populations, basically resulting from the matched play of the dispersión of its parasitic larvae (glochidium and lasidium) by means of the host fishes, with the dragging exerted by the water during the floods. In consequencc, very variable concentrations appear at points that are more favourablc to thc stability of each different species.